News you can use! - November-December 2014 - Colorado State Forest Service, author (Colorado State University. Libraries, 2014)
Electronic newsletter highlighting education, training, events, etc. in regards to Colorado forestry.
Issuing body name changes between the Community Forestry Division and the Urban and Community Forestry Division of the Colorado State Forest Service.